Assisted reproductive technology in Japan: A summary report for 2018 by the Ethics Committee of the Japan Society of Obstetrics and Gynecology. (20th November 2020) - Ishihara, Osamu; Jwa, Seung Chik; Kuwahara, Akira; Katagiri, Yukiko; Kuwabara, Yoshimitsu; Hamatani, Toshio; Harada, Miyuki; Osuga, Yutaka
Abstract: Purpose: Since 2007, the Japan Society of Obstetrics and Gynecology (JSOG) has collected cycle‐based data for assisted reproductive technology (ART) in an online registry. Here, we present the characteristics and treatment outcomes of ART cycles registered during 2018. Methods: The Japanese ART registry consists of cycle‐specific information for all ART treatment cycles implemented at 621 participating facilities. We conducted descriptive analyses for such cycles registered for 2018. Results: In total, 454 893 treatment cycles and 56 979 neonates were reported in 2018: both increased from 2017. The mean maternal age was 38.0 years (standard deviation ± 4.7). Of 247 402 oocyte retrievals, 118 378 (47.8%) involved freeze‐all‐embryos cycles; fresh embryo transfer (ET) was performed in 50 463 cycles: a decreasing trend since 2015. A total of 199 914 frozen‐thawed ET cycles were reported, resulting in 69 357 pregnancies and 49 360 neonates born. Single ET (SET) was performed in 82.2% of fresh transfers and 83.4% of frozen‐thawed cycles, with singleton pregnancy/live birth rates of 97.2%/97.2% and 97.0%/97.2%, respectively. Conclusions: Total ART cycles and subsequent live births increased in 2018. SET was performed in over 80% of cases, and the mode of ET has shifted continuously from using fresh embryos to frozen‐thawed ones compared with previous years.